The Negative Impact of Varicocele on Basic Semen Parameters, Sperm Nuclear DNA Dispersion and Oxidation-Reduction Potential in Semen - Gill, Kamil (Int J Environ Res Public Health, 2021)
Since varicocele is so common in infertile men, this study intends to analyse the relationships between varicocele and conventional semen characteristics, sperm nuclear DNA dispersion and oxidation-reduction potential (ORP) in semen. Varicocele-positive and varicocele-negative infertile men (study groups) showed significantly lower standard sperm parameters and higher sperm DNA fragmentation (SDF) and ORP in semen than healthy volunteers and subjects with proven fertility (control groups). A lower proportion of low SDF levels (0–15% SDF) and higher incidence of high SDF levels (>30% SDF), as well as a higher prevalence of high ORP values (>1.37 mV/10(6) sperm/mL), were found in the study groups vs. the control groups. Moreover, infertile men had significantly lower odds ratios (ORs) for low SDF levels and significantly higher ORs for high SDF levels and high ORP. SDF and ORP were negatively correlated with sperm number, morphology, motility and vitality. Furthermore, a significant positive correlation was found between SDF and ORP. The obtained results suggest that disorders of spermatogenesis may occur in varicocele-related infertility. These abnormalities are manifested not only by reduced standard semen parameters but also by decreased sperm DNA integrity and simultaneously increased oxidative stress in semen.